2004
DOI: 10.1074/jbc.m403329200
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-dependent Degradation of Cyclin D1 in 1-Methyl-4-phenylpyridinium Ion (MPP+)-induced Cell Cycle Arrest

Abstract: 1-Methyl-4-phenylpyridinium ion (MPP ؉), an active metabolite of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, induces cell death and inhibition of cell proliferation in various cells. However, the mechanism whereby MPP ؉ inhibits cell proliferation is still unclear. In this study, we found that MPP ؉ suppressed the proliferation with accumulation in G 1 phase without inducing cell death in p53-deficient MG63 osteosarcoma cells. MPP ؉ induced hypophosphorylation of retinoblastoma protein and rapidly down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…PC12 cells were maintained in RPMI1640 medium (Life Technologies) supplemented with 10% heat-inactivated fetal horse serum (HS) and 5% FCS. HeLa-0 cells were described previously (4). PCR confirmed that these cells are subclones of HeLa-S3 cells that have been cultured with ethidium bromide and lack mitochondrial DNA.…”
Section: Cellsmentioning
confidence: 99%
“…PC12 cells were maintained in RPMI1640 medium (Life Technologies) supplemented with 10% heat-inactivated fetal horse serum (HS) and 5% FCS. HeLa-0 cells were described previously (4). PCR confirmed that these cells are subclones of HeLa-S3 cells that have been cultured with ethidium bromide and lack mitochondrial DNA.…”
Section: Cellsmentioning
confidence: 99%
“…In contrast, several studies have reported increased proteasome activity as observed here. MPP ϩ induces the rapid proteasomal degradation of short-lived proteins such as Ret protein in PC12 cells (42) and cyclin D1 in MG63 osteosarcoma cells and HeLa cells (43). Proteasome activity, when measured with a peptide substrates, is elevated by exposure to 10 or 100 M MPP ϩ for 2 h (44).…”
Section: Discussionmentioning
confidence: 99%
“…The viable cells were also counted using NucleoCounter, as described previously. (17) Flow cytometry. Cell-surface expression of TRAIL-R2 was determined by flow cytometry with an EPICS XL (Beckman Coulter, Miami, FL, USA).…”
Section: Methodsmentioning
confidence: 99%